IMPLEMENTASI SISTEM CUSTOMER RELATIONSHIP MANAGEMENT - Putrianto, Novenda kartika; Widyastuti, Yuanita Maria; Oktiarso, Teguh (Universitas Ma Chung, 2024)
This study discusses the implementation of a Customer Relationship Management (CRM) system at PT XYZ, focusing on the implementation stages within the System Development Life Cycle (SDLC). The primary goal of this study is to enhance the company's operational efficiency through better customer data management, more systematic prospect reporting, and more effective campaign result monitoring. During the implementation process, various stages were carried out, including system development, testing, and deployment in the company environment. The study's results indicate that the CRM implementation successfully improved operational efficiency, particularly in handling customer complaints and providing comprehensive information access. This study also offers important implications for other companies looking to adopt a CRM system, highlighting the importance of thorough planning and user training to maximize system benefits. Further studies are recommended to evaluate the long-term impact of CRM on company performance and to explore the integration of new technologies such as AI and machine learning into the CRM system.